Reliable chromatographic assay for measuring of indoleamine 2,3-dioxygenase 1 (IDO1) activity in human cancer cells - Ilona Sadok; Kamila Rachwał; Ilona Jonik; Magdalena Staniszewska (Taylor & Francis Group, 2021)
The kynurenine pathway is the major tryptophan degradation routes generating bioactive compounds important in physiology and diseases. Depending on cell type it is initiated enzymatically by tryptophan-2,3-dioxygenase (TDO) or indoleamine-2,3-dioxygenase 1 and 2 (IDO1 and IDO2) to yield N-formylkynurenine as the precursor of further metabolites. Herein, we describe an accurate high-pressure liquid chromatography coupled with a diode array detector (HPLC-DAD) method to serve for IDO1 activity determination in human cancer cells cultured in vitro. Enzymatic activity was expressed as the rate of ʟ-kynurenine generation by 1 mg of proteins obtained from cancer cells. Our approach shows the limit of detection and limit of quantification at 12.9 and 43.0 nM Kyn, respectively. Applicability of this method was demonstrated in different cells (ovarian and breast cancer)exposed to various conditions and has successfully passed the validation process. This approach presents a useful model to study the role of kynurenine pathway in cancer biology.